Isolation, genetic, and biological characterization of human adenovirus type 55 positive isolates from Wuhan, China - Jing Xie; Yan Wang; Huan Li; Bingxiu Tan; Zhengying Yu; Lizhong Li; Wei Zhang; Hongbin Song; Leili Jia (BMC Infectious Diseases)
Abstract Background Human adenovirus (HAdV) infection causes acute respiratory diseases in immunocompetent individuals worldwide. Infections by HAdV-55, one of the important pathogens leading to respiratory tract infections, often develop into pneumonia and are frequently associated with outbreaks in military camps and schools. Methods We studied 186 HAdV-55-positive nasopharyngeal swab samples that were collected from patients with respiratory infection in Wuhan, China, from 2018 to 2019. Fifteen samples with high viral loads were selected for viral isolation and cultured with MRC-5 cells. These strains were then whole-genome sequenced to investigate their genetic characteristics by phylogenetic analyses. We then selected three HAdV-55 strains to quantify viral replication and further assessed the pathogenic characteristics of one strain in Syrian hamsters and BALB/c nude mice. Results HAdV-55-174 exhibited the highest replication ability in cultured cells compared to other strains, so this strain was selected for further investigation. Although the hamsters and mice were not so susceptible to HAdV-55-174 infection, viral loads were detected in the lungs and tracheas of the animal models, and persistent HAdV-55-174 replication was only observed in BALB/c nude mice. Histopathological lesions, including a widened alveolar septum and inflammatory cell infiltration, were observed in the lungs and tracheas of HAdV-55-174 infected animals. Conclusion We isolated and characterized the HAdV-55 strains circulating in Wuhan from 2018 to 2019, which may be meaningful for further studies on HAdV-55 infection and pathogenesis.